On real-time velocity control of DC motors by using computer-aided control system design - Meza Sánchez, Marlen; Moreno Valenzuela, Javier (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
In this paper, the advantages of a computer-aided control system design tool, specifically Matlab, are addressed to achieve real-time velocity control of direct current (DC) motors. To this aim, an experimental set-up is proposed, which avoids the use of a data acquisition board by employing the parallel port and two microcontrollers to establish the data feedback between the computer and the DC motor. Attention to the concepts of fast computing and real-time computing is also paid. Experiments confirmed the advantage of using a computer-aided control system design tool as well as the differences in the performance of a control algorithm implemented using fast computing and real-time computing.